Prenatal acupuncture: Women's expectations and satisfaction and influence on labor. Issue 2 (1st February 2018) - Trutnovsky, Gerda; Schneeweiss, Melanie; Pregartner, Gudrun; Reif, Philipp; Lang, Uwe; Ulrich, Daniela
Abstract: Background: Use of prenatal acupuncture for labor preparation is common, but there is still conflicting evidence with respect to its objective obstetric benefits. There is little information on women's expectations and subjective experiences with acupuncture treatments. Methods: In this retrospective cohort study, a validated questionnaire on women's treatment satisfaction was sent to women who had received prenatal acupuncture at the obstetric clinic of the Medical University of Graz, Austria within the last 3 years. The electronic obstetric database was used to extract detailed clinical and obstetric data of women who received acupuncture and delivered at the hospital. For comparison, obstetric data were matched with a control group of women without prenatal acupuncture, who had given birth at the hospital during the study period. Results: The questionnaire was sent to 150 women, out of which 70 (46.7%) completed and returned the questionnaire. Analysis of the questionnaire indicated good overall satisfaction (mean sum score 26.22 ± 4.72) with acupuncture treatment—97.1% indicated that they were very or quite satisfied. Responders did not differ from nonresponders, except for the time between delivery and questionnaire ( P  = .015). Comparisons between the deliveries after prenatal acupuncture (n = 144) and the matched control deliveries (n = 576) showed no statistical significant differences in the length of labor and use of analgesics. Conclusion: Prenatal acupuncture is likely to have positive effects on pregnant women, aside from an objective influence on labor duration and pain.